Islamic Movement in Sudan: itsâ€™ Development and Influence on the Dynamics of Sudan Education - Ribut Nur Huda (EL-TARBAWI, 2022)
The Islamic movement has occupied an important place in Sudan's educational world from its leadership in 1989 till the present. The role of the Islamic Movement seems imbalanced and causes influential people "go their separate ways". In addition to subordination, the Islamic Movement restricts academics' and intellectuals' space to speak the truth and connect people's aspirations. This study is noteworthy in light of the Sudan situation, which has seen the loss of many of its best academicians and the absence of freedom and resources for teaching, research, and publication. This study concludes that the Islamic Movement, which has been in power for more than 30 years, has influenced the decline of scientists' careers in the country and their immigration to other countries to keep working after retirement. This study determines the extent of the political influence of the Islamic Movement on the dynamics of the academic realms. This study also explores the truth of the assumptions of the Sudanese people that â€œthe Sudanese government failed, but the people succeededâ€ by conducting historical and phenomenological analysis associated with the Islamic Movement as an organizational entity as well as a practical political force.